Evolution of Homeologous Gene Expression in Polyploid Wheat - Zhao, Na (Genes (Basel), 2020)
Polyploidization has played a prominent role in the evolutionary history of plants. Two recent and sequential allopolyploidization events have resulted in the formation of wheat species with different ploidies, and which provide a model to study the effects of polyploidization on the evolution of gene expression. In this study, we identified differentially expressed genes (DEGs) between four BBAA tetraploid wheats of three different ploidy backgrounds. DEGs were found to be unevenly distributed among functional categories and duplication modes. We observed more DEGs in the extracted tetraploid wheat (ETW) than in natural tetraploid wheats (TD and TTR13) as compared to a synthetic tetraploid (AT2). Furthermore, DEGs showed higher Ka/Ks ratios than those that did not show expression changes (non-DEGs) between genotypes, indicating DEGs and non-DEGs experienced different selection pressures. For A-B homeolog pairs with DEGs, most of them had only one differentially expressed copy, however, when both copies of a homeolog pair were DEGs, the A and B copies were more likely to be regulated to the same direction. Our results suggest that both cis- and inter-subgenome trans-regulatory changes are important drivers in the evolution of homeologous gene expression in polyploid wheat, with ploidy playing a significant role in the process.